In Situ Deprotection of Polymeric Binders for Solution‐Processible Sulfide‐Based All‐Solid‐State Batteries. Issue 37 (7th August 2020) - Lee, Jieun; Lee, Kyulin; Lee, Taegeun; Kim, Hyuntae; Kim, Kyungsu; Cho, Woosuk; Coskun, Ali; Char, Kookheon; Choi, Jang Wook
Abstract: Sulfide‐based all‐solid‐state batteries (ASSBs) have been featured as promising alternatives to the current lithium‐ion batteries (LIBs) mainly owing to their superior safety. Nevertheless, a solution‐based scalable manufacturing scheme has not yet been established because of the incompatible polarity of the binder, solvent, and sulfide electrolyte during slurry preparation. This dilemma is overcome by subjecting the acrylate (co)polymeric binders to protection−deprotection chemistry. Protection by the  tert ‐butyl group allows for homogeneous dispersion of the binder in the slurry based on a relatively less polar solvent, with subsequent heat‐treatment during the drying process to cleave the  tert ‐butyl group. This exposes the polar carboxylic acid groups, which are then able to engage in hydrogen bonding with the active cathode material, high‐nickel layered oxide. Deprotection strengthens the electrode adhesion such that the strength equals that of commercial LIB electrodes, and the key electrochemical performance parameters are improved markedly in both half‐cell and full‐cell settings. The present study highlights the potential of sulfide‐based ASSBs for scalable manufacturing and also provides insights that protection−deprotection chemistry can generally be used for various battery cells that suffer from polarity incompatibility among multiple electrode components. Abstract : Protection−deprotection chemistry is employed to resolve a dilemma pertaining to polarity compatibility among the binder, solvent, and solid electrolyte for sulfide‐based all‐solid‐state batteries. The polar functional groups of the binder, initially protected by tert ‐butyl groups during the slurry mixing stage, are deprotected when the electrode is dried. The polar binder enhances electrode adhesion and electrochemical performance drastically.